THE ISSUE OF THE ATTITUDE TOWARDS THE JADID MOVEMENT IN BUKHARA AND THE DEVELOPMENT OF PEDAGOGICAL IDEAS IN IT (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the activities of the Bukhara Jadids and the initial goal of the political and public organizations they created - to introduce the nation to its identity, to educate a new generation that will lay the foundation for the independence of the Nation and Motherland through a radical reform of the socio-political system. It is scientifically and theoretically justified that it is aimed at improving all other areas and has made a great contribution to the development of culture and spirituality.